2017
DOI: 10.1007/s12649-017-9870-8
|View full text |Cite|
|
Sign up to set email alerts
|

Ability of Two Dam Fine-Grained Sediments to be Used in Cement Industry as Raw Material for Clinker Production and as Pozzolanic Additional Constituent of Portland-Composite Cement

Abstract: other one is calcined in the range 550-1000 °C aiming to obtain a pozzolanic reactive material that could be used as supplementary cementitious material in blended Portland cement. After thermal treatments, the products are characterized and compared to ordinary Portland cement (OPC) and to pozzolanic active materials (fly ash from pulverized-coal power plant). Results showed that each sediment is suitable for the only tested reuse option. For the clinker prepared with SEP sediment, the morphology and the mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…The same finding was made in Diouri et al's study [17] which showed that using 8% of calcined sediment improves the hydration of the cement-sediment blend and results in mechanical strengths equivalent to those obtained with a CEM I Portland cement. Faure et al's study [18] confirmed this by observing portlandite consumption when calcined sediments were used. Calcined sediments also allow the improvement of the durability of concrete as shown in Safer et al's study [19] where part of the cement (10%, 20% and 30%) was substituted by sediment calcined at 750 °C for 5 hours.…”
Section: Introductionmentioning
confidence: 78%
“…The same finding was made in Diouri et al's study [17] which showed that using 8% of calcined sediment improves the hydration of the cement-sediment blend and results in mechanical strengths equivalent to those obtained with a CEM I Portland cement. Faure et al's study [18] confirmed this by observing portlandite consumption when calcined sediments were used. Calcined sediments also allow the improvement of the durability of concrete as shown in Safer et al's study [19] where part of the cement (10%, 20% and 30%) was substituted by sediment calcined at 750 °C for 5 hours.…”
Section: Introductionmentioning
confidence: 78%
“…Sand content is approximately close. From a given site's perspective, local hydrodynamics also may influence PSD of accumulated sediments, as in a reservoir where the inlet is enriched in coarse particles and the area near the dam is enriched with fine particles [17,18]. From Insert Table 1Table 1, we observe that continental sediments tend to a higher total organic carbon (TOC) content, with a mean content of 4.21 wt.% versus 2.60 wt.% for marine sediments, and a median of 3.40 vs 2.50 wt.%.…”
Section: Main Sediments Characteristicsmentioning
confidence: 99%
“…This is due to the elimination of organic matter (density 1 g/cm 3 ) and the decomposition of limestone (density 2.6-2.8 g/m 3 ) to form calcium oxide (density approximately 3.3 g/cm 3 ). However, a decrease in the density of SF 800 upon increasing the calcination temperature could be due to the recrystallization of the mineral phases [44]. The flash calcination also induces a slight increase in particle size without a reduction in specific surfaces.…”
Section: The Physical Characteristics Of Materialsmentioning
confidence: 99%